Phosphoinositide 3–kinase γ participates in T cell receptor–induced T cell activation - Alcázar, Isabela (The Rockefeller University Press, 2007)
Class I phosphoinositide 3–kinases (PI3Ks) constitute a family of enzymes that generates 3-phosphorylated polyphosphoinositides at the cell membrane after stimulation of protein tyrosine (Tyr) kinase–associated receptors or G protein–coupled receptors (GPCRs). The class I PI3Ks are divided into two types: class IA p85/p110 heterodimers, which are activated by Tyr kinases, and the class IB p110γ isoform, which is activated by GPCR. Although the T cell receptor (TCR) is a protein Tyr kinase–associated receptor, p110γ deletion affects TCR-induced T cell stimulation. We examined whether the TCR activates p110γ, as well as the consequences of interfering with p110γ expression or function for T cell activation. We found that after TCR ligation, p110γ interacts with Gαq/11, lymphocyte-specific Tyr kinase, and ζ-associated protein. TCR stimulation activates p110γ, which affects 3-phosphorylated polyphosphoinositide levels at the immunological synapse. We show that TCR-stimulated p110γ controls RAS-related C3 botulinum substrate 1 activity, F-actin polarization, and the interaction between T cells and antigen-presenting cells, illustrating a crucial role for p110γ in TCR-induced T cell activation.